Deubiquitinating Enzymes in Parkinson’s Disease - Chakraborty, Joy; Ziviani, Elena (Frontiers in Physiology, 2020)
Mitochondrial dysfunction and neurodegeneration have been directly correlated in many neurodegenerative disorders. Parkinson’s disease (PD) in particular has been extensively studied in this context because of its well-characterised association with mitophagy, a selective type of autophagy that degrades mitochondria. Mitophagy is triggered by ubiquitin modification of proteins residing on the surface of mitochondria. Therefore, mitophagy is subject to suppression by deubiquitination. In recent years, many deubiquitinase enzymes (DUBs) emerged as therapeutic targets to compensate hindered mitophagy in PD. It is reasonable that inhibition of specific DUBs should induce mitophagy by blocking deubiquitination of mitochondrial proteins, although the signalling pathway is not always that linear. The broad aspect suggests that there could be cross talks among DUBs, which may in turn have synergistic effect to rescue the disease progression. In this short review we have highlighted DUBs that hold therapeutic value in the field of neurodegenerative diseases, PD in particular